Reactive approach motivation (RAM) for religion.[article]. - McGregor, Ian
In 3 experiments, participants reacted with religious zeal to anxious uncertainty threats that caused reactive approach motivation (RAM) in past research (see McGregor, Nash, Mann, and Phills, 2010 for implicit, explicit, and neural evidence of RAM). In study 1, results were specific to religious ideals and did not extend to merely superstitious beliefs. Effects were more pronounced among the most anxious and uncertainty averse participants in study 1 and among the most approach-motivated participants in study 2 (i. e., with high Promotion Focus, Behavioral activation, Action orientation, and Self-esteem Scale scores). In studies 2 and 3, anxious uncertainty threats amplified even the most jingoistic and extreme aspects of religious zeal. In study 3, reactive religious zeal occurred only among participants who reported feeling disempowered in their everyday goals in life. Results support a RAM view of empowered religious idealism for anxiety management (cf. Armstrong 2000; Inzlicht, McGregor, Hirsch, And Nash, 2009).
Keywords: Anxious uncertainty; idealistic conviction; Religious zeal; Self-esteem.; Reactive approach motivation